Economically accessible vibration vest for respiratory physiotherapy - Amador, Paulo; Negrão, Larissa; Salame, Lucas (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS), 2019)
Respiratory physiotherapy of patients with spinal cord injury is based on a pressure applied to the patient's chest followed by a vibration performed by the physiotherapy professional himself. This paper presents a device for the optimization of respiratory physiotherapy by obtaining higher pressure and frequency of movement execution through digital electronics adapted to an adjustable vest.